MAKANAN ADAT PADA UPACARA BATAGAK KUDO-KUDO DI KECAMATAN VII KOTO SUNGAI SARIAK KABUPATEN PADANG PARIAMAN - Sarah, Devi; Elida, Elida; Syarif, Wirnelis (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This study aimed to describe the circuit implementation, custom food, equipment type, manner of presentation and manner of eating, and the meaning contained in traditional foods. This type of research is descriptive qualitative research locations in the District VII Koto Sariak Sungai Padang Pariaman district. Data collection techniques: observation, interviews and documentation. Data analysis techniques: data reduction, data presentation, and verification conclusion. The results showed (1) Networks ceremony Batagak Kudo Kudo consisting of mangakok days to hang the symbols on houses famine. (2) The type of food that was served at the traditional ceremony Kudo Kudo Batagak indigenous food and staple food. (3) Equipment used for serving food consists of rice cambuang, samba plates, dinner plates, trays, the hood of food, dalamak. (4) How to serve food that is put on the food that has been diporsikan seperah eat. ie ordinances eat makan bajamba. (5) The meaning of the traditional food that contained a moral message to the owner of the house.Keywords: food customs, ceremonies, Batagak-kudo kudo